Net Zeros and Ones: How Data Erasure Promotes Sustainability, Privacy, and Security - Stiennon, Richard (2023)
In Net Zeros and Ones: How Data Erasure Promotes Sustainability, Privacy, and Security, a well-rounded team of accomplished industry veterans delivers a comprehensive guide to managing permanent and sustainable data erasure while complying with regulatory, legal, and industry requirements. In the book, you$1 (Bll discover the why, how, and when of data sanitization, including why it is a crucial component in achieving circularity within IT operations. You will also learn about future-proofing yourself against security breaches and data leaks involving your most sensitive information$1 (Ball while being served entertaining industry anecdotes and commentary from leading industry personalities.s
Keywords: Information security; Computer security